2013
DOI: 10.1504/ijbnn.2013.054515
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle toxicity by the gastrointestinal route: evidence and knowledge gaps

Abstract: The increasing interest in nanoparticles for advanced technologies, consumer products, and biomedical applications has led to great excitement about potential benefits but also concern over the potential for adverse human health effects. The gastrointestinal tract represents a likely route of entry for many nanomaterials, both directly through intentional ingestion or indirectly via nanoparticle dissolution from food containers or by secondary ingestion of inhaled particles. Additionally, increased utilisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
207
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(213 citation statements)
references
References 204 publications
(344 reference statements)
5
207
0
1
Order By: Relevance
“…It has been proved that nanoparticles when used in a high dose could provide toxic results. Several in vivo studies proved that low dose of nanoparticles provides nontoxic results [45]. Nanoparticles which could be used in the treatment of gastric cancer still shows side effects which have been found out by different experimentation.…”
Section: Toxicity Of Nanoparticlesmentioning
confidence: 99%
“…It has been proved that nanoparticles when used in a high dose could provide toxic results. Several in vivo studies proved that low dose of nanoparticles provides nontoxic results [45]. Nanoparticles which could be used in the treatment of gastric cancer still shows side effects which have been found out by different experimentation.…”
Section: Toxicity Of Nanoparticlesmentioning
confidence: 99%
“…Additionally, growing use of NP may lead to increased environmental contamination and unintentional ingestion via water, food animals, or fish [12]. Considering that the small intestine is the site of most nutrient digestion and absorption, including carbohydrates, peptides, and fats as well as it also serves secretory and protective immune functions, alterations of this complex system can exert pleiotropic effects [12]. Indeed, the present study explored the potential effects of TiO 2 NP at small intestine level following in vivo study by repeated oral administration in adult male and female rats, at dose levels relevant to human dietary intake.…”
Section: Introductionmentioning
confidence: 99%
“…46 It has been reported that Cu NPs or CuO NPs have high solubility in acidic milieu (pH 5.5) with high positive zeta potential. 25,35 Thus, the high dissolution and zeta potential of Cu NPs in acidic conditions reflect a considerable interaction of Cu NPs within acidic milieu simulating the stomach.…”
mentioning
confidence: 99%
“…47,48 The rate of dissolution also affects the absorption and biological response of NPs. 46 Comparative kinetic study of zinc oxide (ZnO) and titanium dioxide (TiO 2 ) NPs revealed that the higher absorption and more extensive organ distribution of ZnO NPs might be due to their higher dissolution rate in acidic gastric fluid than TiO 2 NPs, which have minimal dissolution in acidic milieu. 49 It has been reported that Cu levels in serum and kidney of nano-Cu (75 mg/kg)-treated mice are elevated at 24 hours and remain at the higher level until 72 hours when compared to equivalent Cu mass of ion-Cu (147.6 mg/kg, equivalent 70 mg/kg on Cu mass).…”
mentioning
confidence: 99%
See 1 more Smart Citation